2000
DOI: 10.4049/jimmunol.165.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Administration of Anti-CD40 Ligand and Donor Bone Marrow Leads to Hemopoietic Chimerism and Donor-Specific Tolerance Without Cytoreductive Conditioning

Abstract: Transplantation tolerance, defined as allograft acceptance by an immunocompetent recipient in the absence of long-term immunosuppression, has remained an elusive goal in clinical transplantation. Robust experimental tolerance induction strategies have in common methods to induce mixed hemopoietic chimerism. To date, however, chimerism induction across allogeneic barriers has required recipient conditioning with irradiation or cytoablative agents. In this paper we show that B6 recipients of fully allogeneic BAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
205
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(215 citation statements)
references
References 10 publications
8
205
2
Order By: Relevance
“…6,7 In the late 1970s, Slavin et al 8,9 showed that chimerism induced by infusion of allogeneic marrow after total lymphoid irradiation was associated with tolerance to skin grafts of the same donor type. More recent evidence suggests that stable mixed hematopoietic chimerisms can be induced in non-myeloablated animals receiving only immunosuppression before the infusion of allogeneic HSC [10][11][12] or by increasing the number of cells transplanted. 13,14 Engrafted animals usually become tolerant to the donor cells and do not reject subsequent grafts from the same donor.…”
Section: Gene-expressing Cells Were Found In the Grafted Hematopoietimentioning
confidence: 99%
“…6,7 In the late 1970s, Slavin et al 8,9 showed that chimerism induced by infusion of allogeneic marrow after total lymphoid irradiation was associated with tolerance to skin grafts of the same donor type. More recent evidence suggests that stable mixed hematopoietic chimerisms can be induced in non-myeloablated animals receiving only immunosuppression before the infusion of allogeneic HSC [10][11][12] or by increasing the number of cells transplanted. 13,14 Engrafted animals usually become tolerant to the donor cells and do not reject subsequent grafts from the same donor.…”
Section: Gene-expressing Cells Were Found In the Grafted Hematopoietimentioning
confidence: 99%
“…While some form of (local) irradiation was universally required even when very profound doses of T-cell depleting antibodies (anti-CD4 and anti-CD8 mAb) were given as part of the conditioning [9,10], costimulation blockade allowed the elimination of any irradiation from recipient conditioning if very high doses (mega doses) of allogeneic BM were transplanted [7,11]. Anti-CD40L is sufficiently effective alone (without CTLA4Ig) in strain combinations without minor antigen barriers (e.g., donor B10.A → recipient C57BL/10) [12,13] [8,14,18,19]. As long as no effective anti-CD40L mAb is available for clinical use, its elimination from recipient conditioning would be desirable.…”
Section: Experimental Protocols Minimizing Conditioning Avoiding Globmentioning
confidence: 99%
“…Thus, virtually all recently reported mixed chimerism protocols involve anti-CD40L [8,14,18,19]. As long as no effective anti-CD40L mAb is available for clinical use, its elimination from recipient conditioning would be desirable.…”
Section: Experimental Protocols Minimizing Conditioning Avoiding Globmentioning
confidence: 99%
“…It has recently been reported that combined blockade of the CD28 and CD40 co-stimulatory pathways dramatically decreases the amount of recipient conditioning required to achieve hematopoietic macrochimerism (18). In fact, treatment with anti-CD154 alone (19) or in combination with CTLA4-Ig (20) completely eliminated the need for recipient conditioning when very large doses of donor bone marrow were used.…”
Section: Cd154 and Cd40mentioning
confidence: 99%